NALAR MANTIQI DALAM USUL FIQH IMAM AL-SYATIBI: Telaah Muqaddimat Kitab al-Muwafaqat - Zaeni, Ahmad (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
This article aims to trace the extent of the reliability of the logical foundation of Usul Fiqh Imam Syatibi which until now has been developed massively and scientifically accepted from all over the world. In fact, when there was a polemic on the status of Qat'i Usul Fiqh, al-Syatibi went against the current of the majority of scholars who said that Usul Fiqh was Dzonni. Al-Syatibi was of the view that Usul Fiqh was Qat'i. His thinking stating that Usul Fiqh was Qat'i became the forerunner of the independence of maqasid al-syari'ah as an independent branch of science. The data analysis technique to handle this research problem is the Miles and Huberman model. The data analysis method used is content analysis, while the approach used is the philosophy of logic. The results of this research are that the foundation of Usul Fiqh al-Syatibi is Aristotelian logic, he is able to provide a solution to the debate on schools of thought by returning furu' issues to Usul based on the foundation and systematic thinking logically or mantiqi logic.